PARLIAMENTARISM AS A HISTORICAL AND LEGAL CATEGORY - Бородін, Іван Лук’янович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: an attempt has been made to analyze the stages of formation of parliamentarism in connection with the formation and development of statehood, at different stages of development of civilizations, forms of its organizations and functioning. Methods: comparison, analysis, analogy, induction, deduction and others that served as a tool for material selection, and were a necessary condition for achieving this goal. Results: problems of the theory and practice of parliamentarism, as a historical and legal category, are considered from the standpoint of scientific traditions that have developed in the process of research in this area. It is explained that the legal categories, definitions used in the analysis of parliamentarism, as a historical - legal category, take into account in their content the constitutional traditions and norms of other laws, the practice of state and legal construction. Clarifications were made on the understanding of parliamentarism as a social phenomenon, which means the representative principles of governance. Discussion: experience in the development of geopolitical systems shows that the possibility of solving vital problems of national importance in one way or another, to some extent depends on the scale of the invitation to the process of making these decisions. The study of the institution of parliamentarism, forms of its organizations and functioning has always been at the center of scientific research, because parliamentarism is the legal and organizational basis for involving citizens in addressing the most important issues of state building and governance. The theory of separation of powers has become the foundation of future concepts of parliamentarism, as well as the analysis of its elements in modern conditions. Parliamentarism, which must be understood as the representative foundations in the formation of state power and governance - a historical and legal phenomenon, a consequence of the development of socio-political systems. Its emergence, development and formation is associated with the emergence, development and formation of states. In addition, parliamentarism, like any other social phenomenon, has its prehistory, the genotype of which was formed in the early stages of the history of human social existence. The history of civilizations is a silent witness to how empires arose and disappeared, dictatorial and authoritarian regimes disappeared, and the principle of the basis of power was gradually established through parliamentarism. He was and remains the main and so far no alternative has been found. From the point of view of understanding this fundamental principle of the organization of state power, one of the key issues, the object of constant research and study by various sciences, historical and legal science, is certainly the institution of parliamentarism. In addition, one of the reasons for the increased interest of scholars and politicians in the history and development of modern parliamentarism is the existence of a large number of theoretical and practical problems related to the legal and organizational formation of the national parliament, determining its constitutional status and role in government, with the development of national law schools. Therefore, it does not need unnecessary evidence of the need for in-depth analysis of the achievements of jurisprudence, both domestic and foreign, in matters of legal regulation of forms of organization and mechanism of the state as one of the means of stabilizing society, especially in the emerging states. Of course, within one article, as well as previous research by legal scholars and historians, it is impossible to cover all issues related to such a large-scale phenomenon as parliamentarism in its historical and legal sense. At the same time, in the course of our research it became clear that a number of issues of theoretical and practical nature are insufficiently studied and require efforts not only of theoretical - legal, but also of historical - legal nature. For example, in modern legal doctrine there is no single approach to defining the concept of «parliamentarism» as a historical - legal category. It is still unclear how the forms of government and parliamentarism relate to each other. Issues related to the evolution of parliamentarism from antiquity to the present require scientific analysis. The various theoretical constructions of parliamentarism and its principles, the reasons for their evolution, remain insufficiently substantiated. Also, serious scientific analysis, comprehension and generalization require processes of state formation, methods of exercising state power in countries with different forms of government.